Hybrid algorithm for materialised view selection. (30th October 2020) - Mayata, Raouf; Boukra, Abdelmadjid
Data warehouses store current and historical data, which are used for creating reports, for the purpose of supporting decision-making. A data warehouse uses materialised views in order to reduce the query processing time. Since materialising all view is not possible, due to space and maintenance constraints, materialised view selection became one of the crucial decisions in designing a data warehouse for optimal efficiency. In this paper the authors present a new hybrid algorithm named (QCBO) based on both quantum inspired evolutionary algorithm (QEA) and colliding bodies optimisation (CBO) to resolve the materialised view selection (MVS) problem. Also, some aspects of the well-known greedy algorithm (HRU) are included. The experimental results show that QCBO provides a fair balance between exploitation and exploration. Comparative study reveals the efficiency of the proposed algorithm in term of solution quality compared to well-known algorithms.